Fibrolytic efficiency of the large intestine microbiota may benefit running speed in French trotters: A pilot study - Maximilien Vasseur; Romuald Lepers; Nicolas Langevin; Samy Julliand; Pauline Grimm (Physiological Reports)
Abstract This pilot study sought to explore the contribution of the large intestine microbiota to energy metabolism and exercise performance through its ability to degrade fibers into short‐chain fatty acids (SCFAs). To investigate this, a correlational study was carried out on athlete horses under the same management conditions. Fecal microbiota diversity and composition, fibrolytic efficiency and SCFAs were analyzed. An incremental running test was carried out to estimate the maximal running speed (MRS) of the horses, and blood samples were taken to measure energy metabolism parameters. MRS was positively correlated with the efficiency of the fecal microbiota in degrading cellulose in vitro (r = 0.51; p = 0.02). The abundance of fibrolytic bacterial taxa was not associated with MRS, but functional inference analysis revealed a positive association between MRS and pathways potentially related to fibrolytic activity (r = 0.54; p = 0.07 and r = 0.56; p = 0.05 for butyrate metabolism and thiamine metabolism, respectively). In contrast, the metabolic pathway of starch degradation appeared negatively associated with MRS (r = −0.55; p = 0.06). The present findings suggest a potential contribution of the large intestine microbiota and dietary fibers digestion to exercise capacity in equine athletes.